1990
DOI: 10.4049/jimmunol.144.8.3015
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T cell proliferation by IL-7.

Abstract: The regulation of murine T cell proliferation by IL-7 was investigated. Highly purified resting splenic T cells were induced to proliferate in a short term assay by IL-7 in the presence of the comitogen, Con A. The proliferation of these resting T cells showed both IL-2-dependent and -independent components as determined by the susceptibility of the response to the blocking effects of anti-IL-2 mAb. Furthermore, IL-7 was found to augment the Con A-induced production of IL-2 and expression of IL-2R by resting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, there have been conflicting results regarding the role of IL-7/IL-7R in Treg development. While IL-2 is known to play a crucial role in Treg homeostasis [ 42 ], it has been discovered that CD25-deficient Tregs rely on IL-7 for survival in the absence of IL-2 [ 43 ]. On the other hand, some studies have indicated that IL-7Rα alone is not enough to promote mature Treg development [ 44 ].…”
Section: Biological Functions Of Il-7mentioning
confidence: 99%
“…However, there have been conflicting results regarding the role of IL-7/IL-7R in Treg development. While IL-2 is known to play a crucial role in Treg homeostasis [ 42 ], it has been discovered that CD25-deficient Tregs rely on IL-7 for survival in the absence of IL-2 [ 43 ]. On the other hand, some studies have indicated that IL-7Rα alone is not enough to promote mature Treg development [ 44 ].…”
Section: Biological Functions Of Il-7mentioning
confidence: 99%
“…Interleukin-7 (IL-7), a potent cytokine for lymphoid cells at the pre-B stage of development, was recently purified and cloned from bone marrow stromal cells. It induces proliferation but not differentiation of pre-B cells (29,38), and also has growth stimulatory effects on early and mature T-cells (6,15,37,47). A receptor for IL-7 was recently cloned and shown to be expressed on pre-B cells, progenitors to pre-B cells, and some myeloid and T cells, but not on mature B cells (14,40).…”
mentioning
confidence: 99%